A widely tunable fiber ring laser with closed loop control based on high-precision stepper motor - 王丽丽 忻向军 朱林伟 (Optoelectronics letters, 2016)
A tunable single-longitudinal mode erbium-doped fiber ring laser based on stepper motor and closed loop control is proposed and demonstrated. The system consists of an erbium-doped fiber （EDF）, a tunable fiber Bragg grating （FBG） filter and a wavelength detector. The characteristics of output laser, such as output power, power stability and 3-dB linewidth, are investigated in the operation range of I 531-1 569 nm. The repeated experimental results of the fiber laser show that the 3-dB linewidth is less than 17 ps, the side-mode suppression ratio （SMSR） is up to 60 dB, the outout Dower is up to 1.37 dBm. and the Dower variation is less than 0.61 dR